Design for Optimization of Solatube Lighting System and Lights with GA-PID Controller - Setya Dwi Koerniawan; Andi Adriansyah; Shamsudin, Abu Ubaidah (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
Solatube is a pipe casing used to channel sunlight from the roof of a building into an enclosed space. The advantage of using Solatube is that it can avoid excess light being directed. However, there is no mechanism for controlling the intensity of sunlight entering the room through the Solatube. By adding control settings, the intensity of incoming sunlight can be adjusted so that it can help visually comfort. It is necessary to control the opening and closing valves to adjust the power of the light produced by the Solatube and the lamp. So, it is needed to design an optimal lighting source to regulate the quantity of light received by the room and the people in the room. The paper aims to achieve good control results by valve controlling using PID control which tunes the parameter by the Genetic Algorithm. Thus, the light intensity entering the room will be stable 24 hours a day. So, that eye comfort, visual coolness and energy savings can be achieved.